A Practical Approach to the Evaluation of Gastrointestinal Tract Carcinomas for Lynch Syndrome. (April 2016) - Pai, Rish K.; Pai, Reetesh K.
Abstract : Lynch syndrome accounts for roughly 1 of every 35 patients with colorectal carcinoma, making it the most common hereditary form of colorectal carcinoma. Identifying patients at risk for Lynch syndrome is essential, as these patients can develop additional Lynch syndrome–related tumors, and patients and their relatives benefit from genetic counseling. The hallmark of Lynch syndrome–associated neoplasms is DNA mismatch repair protein deficiency. In most instances, the pathologist is the first to identify patients at risk for Lynch syndrome and is tasked with communicating these results to treating clinicians and genetics counselors. This review will attempt to provide the tools for pathologists to identify patients at risk for Lynch syndrome through evaluation of tumors of the gastrointestinal tract and provide up-to-date knowledge on evaluating mismatch repair protein deficiency in tumors of the gastrointestinal tract.